The Training Needs of Security Personnel Participating inThe Hajj and Umrah Seasons and their Role in Improving their Performance - Talal Damanhuri, Bassam (The Arab Journal of Administration, 2022)
The study aimed to examine the training needs for security personnel participating in the Hajj and Umrah seasons and their role in developing and improving their performance from the point of view of the leadership and the security personnel themselves, proposals to meet them and reveal the degree of statistically significant differences regarding training needs according to the variables: job, educational level, years of experience, The number of training courses. to achieve these goals, the study used the descriptive analytical method, and the questionnaire as a tool for data collection. The study community represented all security personnel participating in the Hajj and Umrah seasons. The study was applied to a random sample of (748) individuals. The study found that the study sample members agreed on the training needs represented in: communication skills, administrative and technical skills, self-development skills with a degree of approval (strongly agree), and the study sample members agreed to proposals to meet the training needs of security personnel participating in Hajj and Umrah with a degree of approval (agree). severely). The study concluded that there are no statistically significant differences about training needs according to the educational level variable in all dimensions of training needs except for the self-development skills dimension in favor of a secondary education category. There are no statistically significant differences regarding training needs according to the variable of the job, years of experience, and the number of training courses. The study recommends the need to pay attention to evaluating the training needs of security personnel participating in the Hajj and Umrah seasons, periodically and continuously, in order to help identify the changing training needs.